Complete chloroplast genome of Clematis taeguensis (Ranunculaceae), an endemic species from South Korea. Issue 4 (3rd April 2021) - Park, Beom Kyun; Ghimire, Balkrishna; Ha, Young-Ho; Son, Dong Chan; Kim, Dong-Kap
Abstract: The complete chloroplast (cp) genome sequence of Clematis taeguensis Y.N.Lee (Ranunculaceae) was determined to be 159, 534 bp in length, consisting of large (79, 326 bp) and small (18, 338 bp) single-copy regions and a pair of identical inverted repeats (30, 935 bp). The genome contains 92 protein-coding genes, 32 tRNA genes, 8 rRNA genes, and 1 pseudogene ( inf A). Phylogenetic analysis of 19 taxa inferred from the chloroplast genome showed a relationship with C. taeguensis, which is also recognized as a species endemic to the Korean Peninsula. The complete cp genome sequence of C. taeguensis reported here provides important information for future phylogenetic and evolutionary studies in Ranunculaceae.